Intervening with peer ecology: the impact of cooperative learning on peer acceptance, empathy and pupils' experiences of bullying in school - Faizey, Rachel (2019)
Cooperative Learning (CL) is a peer-mediated, instructional intervention with students working together to accomplish shared learning goals (Johnson & Johnson, 2000). The study aimed to build upon existing CL and Peer Acceptance (PA) research and extend this by looking more specifically at whether CL, through the promotion of positive interdependence, could have beneficial outcomes for bullying and associated factors such as empathy.